Post COVID-19 invasive mucormycosis and actinomycosis co-infection: a case report - Mishra, Neha; Mutya, Venkata Sai Shashank; K., Irfan Ibrahim; Rai, Girish (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Actinomyces are commensals of human oropharynx and actinomycosis is considered mainly as an endogenous infection that is triggered by a mucosal lesion. Typically, the disease presents as a slowly progressive painless indurated mass evolving into multiple abscesses with draining sinus tracts sometimes expressing a typical yellow exudate with characteristic sulfur granules. The gold standard of diagnosis is histological examination and bacterial culture of the tissue. Most isolates are susceptible to beta lactams and they are the treatment of choice along with surgical management with drainage of abscesses and excision of recalcitrant fibrotic lesions and debridement of necrotic bone tissue. Here we present a case of 37-year-old male patient who has developed severe COVID-19 infection following which he developed invasive mucormycosis followed by actinomycosis. We postulate that the lymphopenia and the use of immunosuppressants used in treatment of COVID-19 lead to mucormycosis and aggressive debridement used as a strategy in treatment of mucormycosis led to colonization of actinomyces leading to cervicofacial actinomycosis.